Envisioning better blocks for St. Joe: design proposals by Kansas State University landscape architecture students, in collaboration with the City of St. Joseph and Mo-Kan Regional Council - (:unkn) unknown (Kansas State University. College of Architecture, Planning & Design, Department of Landscape Architecture and Regional & Community Planning, 2014)
This compilation presents the landscape architecture studio works of 14 mid-level students in the Master’s of Landscape Architecture program at the Department of Landscape Architecture and Regional & Community Planning at Kansas State University. The studio was taught by Professors Blake Belanger and Alpa Nawre in the spring of 2014 and focused on issues of contemporary site planning and landscape architecture in the context of urban infill development in St. Joseph, Missouri.
Keywords: St. Joseph, Missouri; Landscape architecture; Site planning; Urban development